Aquatic macrophytes as drivers of multiple aspects of fish community: trophic, functional and taxonomic fish responses in tropical and temperate freshwater ecosystems. - Quirino, Bárbara Angélio (2022)
Macrophytes are widely recognized for increasing habitat complexity and driving a relevant role in structuring communities in aquatic ecosystems. We investigated how the density, coverage and diversity of macrophytes can influence multiple aspects of fish community, including functional alpha and beta diversity, foraging efficiency, trophic niche breadth and overlap, total abundance and biomass of fish, as well as of certain species and sizes of fish. We used 30 macrophyte stands sampled in the littoral zone of a tropical river, as well as a dataset of 88 shallow temperate lakes. In the latter case, two spatial scales were considered (lake and points within a lake), since there is usually a negative relationship between fish and macrophyte coverage, and this relationship may be more evident at the point scale, while the effect is attenuated at the lake scale. The results showed that macrophytes can select functional characteristics of fish communities and influence their alpha and beta functional diversity. The highest values of functional alpha diversity occurred in intermediate macrophyte density and high macrophyte diversity. The variation in macrophyte density was strongly responsible for variations in functional beta diversity. Fish showed general trophic responses to the variation in macrophyte attributes, but these responses also depended on fish feeding habits, with herbivores niche breadth responding in the opposite way to omnivores. The increase in macrophyte density led to an increase in fish consumption of higher plants and foraging efficiency, and reduced trophic niche breadth. Fish niche overlap was higher at intermediate levels of macrophyte density. Fish responses depended on fish species identity, lake productivity and water depth. The deeper and more eutrophic the lakes, the more fish tended to occupy macrophyte-covered points within a lake. The results emphasize how aquatic plants can affect the fish community by influencing swimming, food availability and interactions between species, and that the relationship between fish and macrophytes can vary according to the scale of the study and the fish characteristics. The application of the results obtained here has great potential to help in projects of management and conservation of biodiversity, and in the choice of the best configurations of macrophyte stands for the maintenance of ichthyofauna.